First Bite Syndrome Relief With Trigeminal Nerve Branch Block and Ablation: A Case Report. Issue 3 (November 2020) - Kesayan, Tigran; Brock, Charles; Shah, Neal A.; Padalia, Devang
Abstract : First bite syndrome (FBS) is intense facial pain at the first bite of each meal. Currently, no guidelines exist for treating FBS, although botulinum toxin injection has shown benefit. We describe a case of right-sided FBS and painful trigeminal neuropathy, in which FBS resolved for 2 weeks using maxillary and mandibular nerve block and radiofrequency nerve thermal ablation (RFA). Our treatment may have disrupted somatic sensory input from the parotid carried by the auriculotemporal nerve or lesioned the otic ganglion resulting in decreased parasympathetic hyperactivation. Further studies are warranted to evaluate the use of this procedure for FBS.